All-pay auctions: Implementation and optimality - Stefan Jönsson; Armin Schmutzler (University of Zurich, Department of Economics, 2013)
This paper analyzes how all-pay auctions with endogenous prizes can be used to provide effort incentives. We show that wide classes of effort distributions can be implemented as equilibrium outcomes of such games. We also ask how all-pay auctions have to be structured so as to induce high expected highest efforts without generating excessive wasteful efforts of losers. All-pay auctions with endogenous prizes can do better than all-pay auctions with fixed prizes in this respect, in particular, when the prize function is approximately linear. We use the results to compare patents and prizes as innovation incentives, and to explore promotion incentives in organizations.
Keywords: D44; D43; D02; 330; contests; all-pay auctions; endogenous prizes; implementation; Auktionstheorie; Leistungsanreiz; Extensives Spiel; Theorie